Therapies in Aicardi–Goutières syndrome. (January 2014) - Crow, Y. J.; Vanderver, A.; Orcesi, S.; Kuijpers, T. W.; Rice, G. I.
Summary Aicardi–Goutières syndrome (AGS) is a genetically determined disorder, affecting most particularly the brain and the skin, characterized by the inappropriate induction of a type I interferon‐mediated immune response. In most, but not all, cases the condition is severe, with a high associated morbidity and mortality. A number of important recent advances have helped to elucidate the biology of the AGS‐related proteins, thus providing considerable insight into disease pathology. In this study, we outline the clinical phenotype of AGS, paying particular attention to factors relevant to therapeutic intervention. We then discuss the pathogenesis of AGS from a molecular and cell biology perspective. Finally, we suggest possible treatment strategies in light of these emerging insights.